Beyond competence: negotiating identity and agency in the professional development of student psychometrists - Hagen, Sean; Van Deventer, Vasi; van Eeden, René (South African journal of psychology, 2021)
Professional training in Psychology in South Africa is focussed extensively on developing the knowledge and skills required for professional practice. However, although attaining the required levels of knowledge and skills is a necessary condition for professionalism, it is not sufficient. Professionalism requires agential action beyond knowledgeable and skilful behaviour. The aim of this study was to explore how and to what extent the practical placements of student psychometrists contributed to the development of professionalism. Using purposive sampling, the portfolios and supervisor reports of 12 students were selected for analysis. A hybrid model of analysis was employed using thematic analysis, discourse analysis, and positioning theory. Thematic analysis confirmed the discursive context as one of knowledge and skill development, which manifested as an expert–novice discourse within the texts. The discourse offered four subject positions, hierarchically related in mentor–mentee and insider–outsider configurations, supporting an apprenticeship model of increased socialisation into professional practice. However, the outsider position warranted a student–client positioning in a democratic relationship that resisted and disrupted the hierarchical relationships of the expert–novice discourse, demonstrating the presence of agential actions characteristic of professionalism. In conclusion, it is argued that such disruptions of mentor–mentee and insider–outsider positioning should be tolerated and accommodated in practical training settings.